Optimalisasi Potensi Kecamatan Margacinta Dalam Rangka Persaingan Daerah - Rachmawati, Hayuni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
I looked at my own district named Margacinta, which vision is as secondary centre supporting the Gedebage primary Centre the district is also developed to become a servicing area whose mottoâ€™s â€œBERBUDAYAâ€ it also to become the support centre for Bandung City, whose motto is â€œBERMARTABATâ€ to take a part in increasing the economic growth. In the era of regional autonomous, one of which goals is to developt small and middle enterprise in the field of agrobusiness, agroindustry and tourism i have identified. The district,s potency for anticipating the 3 field of business. One of the districtâ€™s 2008 strategic plans, is to realize the green district. Some alternative locations for building those 3 field enterprises on, and the most appropriate is the village is still are housing. Return on investment of the business were discussed as well in the article. However, about investor depend on the districtâ€™s political will.